North Sumatera Ethnic-Based Decision-Making Model to Develop Leadership Abilities for Student Communities - Simaremare, Aman; Wau, Yasaratodo; Hutagalung, Trisnawati; Tambunan, Husna P (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
Study This aiming for dig influence ethnic in taking decisions and development ability leadership among​ student Faculty Faculty of Education (FIP) State University of Medan (UNIMED). With use approach qualitative and studies case, research This involving student active from various ethnic groups, namely Batak, Malay, and Minangkabau. Data was collected through interview in-depth, observation, and documentation. Research results show that ethnic influence method student in take decision, where Batak students are more tend use approach authoritative, while student Malay and Minangkabau are at the forefront deliberation and consensus. In addition, the findings also revealed that style leadership Students at FIP UNIMED vary in accordance with background behind ethnic they. Leader from Batak ethnicity more nature firm and fast in take decision, while leader from ethnic Malay and Minangkabau more focus on collaboration and inclusivity. Diversity ethnic This give challenge at a time opportunity in development more leadership​ holistic. Therefore that, development ability leadership at FIP UNIMED is necessary consider diversity ethnic as part from learning strategies that can enrich perspective and skills student in face dynamics more social​ wide.